Effect of single layer centrifugation using Androcoll-E-Large on the sperm quality parameters of cooled-stored donkey semen doses. (28th November 2013) - Ortiz, I.; Dorado, J.; Ramírez, L.; Morrell, J. M.; Acha, D.; Urbano, M.; Gálvez, M. J.; Carrasco, J. J.; Gómez-Arrones, V.; Calero-Carretero, R.; Hidalgo, M.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of this study was to determine the effect of single layer centrifugation (SLC) using Androcoll-E-Large on donkey sperm quality parameters after 24 h of cool-storage. Ejaculates were collected from Andalusian donkeys and then cooled at 5°C. SLC was carried out after 24 h of cool-storage using Androcoll-E-Large. In the first experiment, all sperm parameters assessed (total and progressive sperm motility, viability, sperm morphology and sperm kinematics VCL, VSL, VAP, LIN, STR, WOB, ALH and BCF) were statistically compared between semen samples processed or not with Androcoll-E-Large. Significant differences (P<0.05) were found between SLC-selected and unselected semen samples for all parameters assessed, obtaining better results after SLC. In the second experiment, semen samples were classified in two groups according to their sperm progressive motility (PM) before SLC. Then, the increments obtained in semen quality parameters after SLC were compared between groups. No significant differences were found between groups, indicating that SLC improved the sperm quality parameters of entire set of semen samples processed with independence to their original PM. In conclusion, SLC with Androcoll-E-Large can be used in donkeys, increasing the sperm quality of cooled-stored donkey semen doses after 24 h of cool storage.